2021
DOI: 10.6004/jnccn.2021.0013
|View full text |Cite
|
Sign up to set email alerts
|

NCCN Guidelines Insights: Non–Small Cell Lung Cancer, Version 2.2021

Abstract: The NCCN Clinical Practice Guidelines in Oncology (NCCN Guidelines) for Non–Small Cell Lung Cancer (NSCLC) address all aspects of management for NSCLC. These NCCN Guidelines Insights focus on recent updates to the NCCN Guidelines regarding targeted therapies, immunotherapies, and their respective biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
606
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 796 publications
(675 citation statements)
references
References 55 publications
8
606
0
5
Order By: Relevance
“…Alectinib is useful as the first‐line chemotherapy with or without brain metastases because of its higher efficacy and milder adverse events than lorlatinib. Moreover, lorlatinib is recommended as a second‐line treatment for symptomatic ALK‐ positive NSCLC patients with CNS relapse after alectinib [1]. However, in ALK‐ positive NSCLC patients with CNS relapse, carcinomatous meningitis and uncontrollable symptomatic epilepsy cause consciousness disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alectinib is useful as the first‐line chemotherapy with or without brain metastases because of its higher efficacy and milder adverse events than lorlatinib. Moreover, lorlatinib is recommended as a second‐line treatment for symptomatic ALK‐ positive NSCLC patients with CNS relapse after alectinib [1]. However, in ALK‐ positive NSCLC patients with CNS relapse, carcinomatous meningitis and uncontrollable symptomatic epilepsy cause consciousness disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the appreciable efficacy and mild adverse events, alectinib is useful as the first‐line chemotherapy for patients with anaplastic lymphoma kinase ( ALK ) gene rearrangement‐positive non‐small cell lung cancer ( ALK‐ positive NSCLC) [1]. Lorlatinib or systemic chemotherapy is recommended as a second‐line treatment for patients with symptomatic ALK‐ positive NSCLC exhibiting central nervous system (CNS) relapse upon failure of alectinib treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, our present study also provided the potential novel target in the investigation through disrupting ANRIL-ATR complex to conquer lung cancer. As indicated in NCCN guideline 2021, radiotherapy and adjuvant chemo-radiotherapy represent important strategies in the treatments of NSCLC [ 16 ]. However, cancer cells usually become to be concomitantly resistant along radiotherapy.…”
Section: Main Textmentioning
confidence: 99%
“…In DestinyLung01 study covering with 42 relapsed/refractory HER2-mutant NSCLC, T-DXd led to a confirmed objective response rate (ORR) of 61.9% and median PFS was 14.0 months (50). FDA already granted a breakthrough therapy designation to T-DXd for the treatment of patients with metastatic HER2-mutant NSCLC (51).…”
Section: Trastuzumab and Its Conjugationmentioning
confidence: 99%